Genetic patterns reveal geographic drivers of divergence in silvereyes ( Zosterops lateralis) - Radu, A; Dudgeon, C; Clegg, SM; Foster, Y; Levengood, AL; Sendell-Price, AT; Townsend, KA; Potvin, DA (Nature Research, 2024)
Identifying mechanisms that drive population divergence under varying geographic and ecological scenarios can inform our understanding of evolution and speciation. In particular, analysis of genetic data from island populations with known colonisation timelines allows us to identify potential source populations of diverging island subspecies and current relationships among populations. Silvereyes (Zosterops lateralis) are a small passerine that have served as a valuable study system to investigate evolutionary patterns on both large and small geographic scales. We examined genetic relatedness and diversity of two silvereye subspecies, the mainland Z. l. cornwalli and island Z. l. chlorocephalus, and used 18 077 single nucleotide polymorphisms (SNPs), to compare locations across southeast Queensland, Australia. Although silvereyes are prolific island colonisers our findings revealed population divergence over relatively small spatial scales was strongly influenced by geographic isolation mediated by water barriers. Strong genetic connectivity was displayed between mainland sites, but minimal inter-island connectivity was shown despite comparable sampling distances. Genetic diversity analysis showed little difference in heterozygosity between island and mainland populations, but lower inbreeding scores among the island populations. Our study confirmed the range of the Z. l. chlorocephalus subspecies throughout the southern Great Barrier Reef. Our results show that water barriers and not geographic distance per se are important in driving incipient divergence in island populations. This helps to explain the relatively high number of phenotypically differentiated, but often geographically proximate, island silvereye subspecies compared to a lower number of phenotypically less well-defined Australian continental subspecies.